Molecular Analysis of the Bloodmeals of Culex spp. Mosquitoes at Natural Habitats in Singapore to Investigate the Potential Risk of Japanese Encephalitis Virus and West Nile Virus Transmission - Yeo, Gladys; Chan, Sharon; How, Choon Beng; Humaidi, Mahathir; Lim, Xiao Fang; Mailepessov, Diyar; Chong, Chee Seng; Phua-Lam, Sai Gek; Lee, Ruth; Hapuarachchi, Hapuarachchige Chanditha; Ng, Lee Ching; Yap, Grace (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2020)
Japanese encephalitis virus (JEV) and West Nile virus (WNV) are arboviruses primarily transmitted by spp. mosquitoes. Birds are the primary hosts for JEV and WNV. Recent WNV outbreaks in Europe and United States and their association with migratory birds highlight the importance of understanding the feeding host preference of potential vectors for outbreak preparedness, especially in nonendemic settings. Singapore is nonendemic to JEV and WNV, but is a stopover site for migratory birds of the East Asian-Australasian Flyway. Therefore, we elucidated the feeding host range of spp. mosquitoes captured in four natural (bird) habitats in Singapore from January 2011 to December 2012. We characterized feeding host DNA in field-caught mosquitoes using a PCR sequencing-based assay targeting the mitochondrial gene regions. Of 22,648 mosquitoes captured, 21,287 belonged to the subgroup. The host DNA analysis showed that mosquitoes from the subgroup are opportunistic biters, feeding on a range of birds and mammals. subgroup, and , was primarily ornithophagic, although they fed opportunistically on mammals, including humans. and , in contrast, fed mainly on mammals. The presence of ornitho- and anthropophilic mosquito vectors and susceptible avian and mammalian hosts poses a risk spill-over transmission of JEV and WNV among humans, should these viruses be introduced through migratory birds and establish persistent transmission in resident birds and animal hosts in Singapore.